2021
DOI: 10.1186/s13256-021-02664-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-transcription intermediary factor 1 gamma (TIF1γ) antibody-positive dermatomyositis associated with ascending colon cancer: a case report and review of the literature

Abstract: Background Anti-transcriptional intermediary factor 1 gamma (TIF1γ) antibody is a marker for predicting cancer association in patients with dermatomyositis (DM). The overall survival rate in DM patients with cancer was reported to be considerably worse than that in DM patients without cancer. However, the treatment for cancer-associated DM remains controversial, because the treatment priority between surgical resection for the tumor and internal treatments, including glucocorticoids, immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Hydroxychloroquine is an antimalarial effective in controlling skin diseases in up to 75% of cases. In cancer-associated DM, it is important to treat the cancer to appropriately manage the disease [12]. Our patient improved with both these agents, corticosteroids and hydroxychloroquine, with cutaneous symptoms having resolved after surgery and restart of the treatment.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hydroxychloroquine is an antimalarial effective in controlling skin diseases in up to 75% of cases. In cancer-associated DM, it is important to treat the cancer to appropriately manage the disease [12]. Our patient improved with both these agents, corticosteroids and hydroxychloroquine, with cutaneous symptoms having resolved after surgery and restart of the treatment.…”
Section: Discussionmentioning
confidence: 80%
“…In people over 40 years old, there is a great risk of malignancy (4.6-to 6-fold higher than the general population) [9,10]. Management of malignancy-associated DM is difficult to attain, with no guidelines defining the best timing for either cancer-directed surgery or glucocorticoid/immunosuppressive therapy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tumour-associated antigens may be produced by inflammatory cells and their production may be increased in rheumatoid arthritis and other autoimmune diseases 14 , 15 , 16 . Transcriptional intermediary factor gamma antibody (TIF1γ), which is considered as precancerous factor 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for cancer in previous case reports included surgical resection and chemo-radiotherapy. Ono et al searched PubMed to identify English-language case reports of anti-TIF1-γ antibody-positive DM with malignancy and suggested that the response may change depending on the treatment modality ( 25 ). Regarding the relationship between the initial treatment and outcome, initial surgical treatment led to better outcomes (p=0.0007, Pearson's chi-square test).…”
Section: Discussionmentioning
confidence: 99%